(untitled) (The Research of Medical Science Review, 2024)
This study was conducted in the pediatric ward of Lady Reading Hospital (LRH) with the primary objective of understanding the treatment protocols for dehydrated children and assessing their nutritional status. The findings revealed that diarrhea was more prevalent in females, accounting for 69.6% of cases. Anthropometric data indicated that the mean age of registered children was 21 ± 23 months. Their mean weight at admission was 5.5 ± 2.41 kg, which increased to 5.7 ± 2.5 kg at discharge. The mean height was recorded at 66.6 ± 9.88 cm. Key risk factors for diarrhea included cessation of breastfeeding due to a subsequent pregnancy, reliance on formula milk as a substitute for breast milk, and the introduction of complementary feeding at inappropriate ages. The mean number of children per family was 3.61 ± 1.97. Notably, breastfeeding initiation was delayed, with mother’s milk typically offered 18 hours after birth. Additionally, 91% of respondents reported administering ghutti after birth. The mean volume of ReSoMal provided to dehydrated patients was 300 ± 268 ml. The study highlights the need for more scientifically robust research to better identify and correlate these risk factors with diarrheal prevalence and nutritional outcomes in pediatric patients.